Molecular and Functional Analyses of the Gene (eshA) Encoding the 52-Kilodalton Protein of Streptomyces coelicolor A3(2) Required for Antibiotic Production - Kawamoto, Shinichi (American Society for Microbiology, 2001)
Analysis of proteins recovered in the S100 precipitate fraction of Streptomyces griseus after ultracentrifugation led to the identification of a 52-kDa protein which is produced during the late growth phase. The gene (eshA) which codes for this protein was cloned from S. griseus, and then its homologue was cloned from Streptomyces coelicolor A3(2). The protein was deduced to be 471 amino acids in length. The protein EshA is characterized by a central region that shows homology to the eukaryotic-type cyclic nucleotide-binding domains. Significant homology was also found to MMPI in Mycobacterium leprae, a major antigenic protein to humans. The eshA gene mapped near the chromosome end and was not essential for viability, as demonstrated by gene disruption experiments, but its disruption resulted in the abolishment of an antibiotic (actinorhodin but not undecylprodigiosin) production. Aerial mycelium was produced as abundantly as by the parent strain. Expression analysis of the EshA protein by Western blotting revealed that EshA is present only in late-growth-phase cells. The eshA gene was transcribed just preceding intracellular accumulation of the EshA protein, as determined by S1 nuclease protection, indicating that EshA expression is regulated at the transcription level. The expression of EshA was unaffected by introduction of the relA mutation, which blocks ppGpp synthesis.